Evaluation of memantine's efficacy and safety in the treatment of children with autism spectrum disorder: A systematic review and meta‐analysis. (21st March 2022) - Elnaiem, Walaa; Benmelouka, Amira Yasmine; Elgendy, Ali Mohamed Naguib; Abdelgalil, Mahmoud Shaban; Brimo Alsaman, Muhamad Zakaria; Mogheeth, Aly; Ali, Mahmoud M.; Yousof, Shimaa Mohammad
Abstract: Background: The United States Food and Drug Administration has approved drugs that address only autism‐related symptoms rather than the underlying impairments. N‐Methyl‐D‐Aspartate receptor antagonists have recently emerged as a promising treatment option for a variety of neurologic and developmental problems, including autism. Aims: To review (systematically), for the first time, the medical literature that explores the safety in and efficacy of memantine in autism. Methods and procedures: A comprehensive electronic search for relevant randomized controlled trials was conducted in four databases. Using RevMan software, we extracted and pooled data as a risk ratio (RR) or normalized mean differences in an inverse variance strategy. Results: This systematic review and meta‐analysis includes five trials. There was no difference in enhancing social responsiveness when compared to placebo, though memantine lowered the likelihood of anxiety (RR = 0.25; 95% Confidence interval: [0.07; 0.87], p = 0.03). However, memantine aggravated impulsive behaviors. Additionally, in another trial that compared memantine added to risperidone versus risperidone added to placebo, memantine was found to be effective and safe. Conclusion: Memantine showed safety in reducing acute symptoms of anxiety and other symptoms encountered in pediatric patients with autism spectrum disorders. However, memantine does not improve the core symptoms of autism. Nevertheless, further long‐term trials are needed to explore its potential efficacy.